(untitled) (Research, Society and Development, 2023)
Paxlovid is an oral medication consisting of two active principles, nirmatrelvir and ritonavir, which act by preventing the viral replication of Sars-CoV-2 through the reversible inhibition of the 3Clpro protease. Developed in a short period of time by Pfizer, paxlovid was temporarily authorized on an experimetal basis by ANVISA for the treatment of Covid-19 in adults who do not require the use of supplemental oxygen and who are at high risk of developing serious complications. Thus, the objective of the work was to present a review of paxlovid in the treatment of Covid-19, an overview of the pharmacological properties, including pharmacodynamics, pharmacokinetics and potential drugs interactions, its development and implications for pharmaceutical practice. This is a literature review of the narrative type, based on the results of a bibliographical research carried out on the PubMed platform between february 18th and 20th, 2023, processed in three stages: identification, screening and inclusion. A total of 708 articles were identified and approximately 3.24% of the total sample was selected for review. The addition of the article Covid-19: pathophysiology and targets for therapeutic intervention was validated, resulting in a final sample of 24 selected articles. With its efficacy, effectiveness and safety well clarified by several clinical studies and in the light of pharmacology, paxlovid represents a fundamental tool in the fight against the Sars-CoV-2 virus, however, the pharmacist must perform a critical management, considering the risk and the potential for pharmacological interactions between paxlovid and other drugs.